2021
DOI: 10.1002/smll.202101180
|View full text |Cite
|
Sign up to set email alerts
|

A Photosensitive Polymeric Carrier with a Renewable Singlet Oxygen Reservoir Regulated by Two NIR Beams for Enhanced Antitumor Phototherapy

Abstract: Scheme 2. Conventional fractional PDT (fPDT) with intermittent light irradiation allowing oxygen replenishment between two PDT cycles; the designed enhanced-fPDT with sustained 1 O 2 generation and additional PTT between two PDT cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…The results showed that FD–Mn–FD had good biocompatibility with negligible damage to the vital organ tissues. Meanwhile, the tumor tissue in the FD–Mn–FD + light group was seriously damaged, while the other seven groups of tumor tissues did not appear damaged or undergo necrosis, indicating that FD–Mn–FD has excellent antitumor properties under irradiation. We also measured the Mn content in the vital organs and tumor sites of mice in different time periods by inductively coupled plasma mass spectrometry (ICP-MS), and MnCl 2 and PBS were used as analytical benchmarks. After orthotopic injection of 200 μL of FD–Mn–FD in mice, the content of Mn 2+ in the tumor site gradually decreased with time.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that FD–Mn–FD had good biocompatibility with negligible damage to the vital organ tissues. Meanwhile, the tumor tissue in the FD–Mn–FD + light group was seriously damaged, while the other seven groups of tumor tissues did not appear damaged or undergo necrosis, indicating that FD–Mn–FD has excellent antitumor properties under irradiation. We also measured the Mn content in the vital organs and tumor sites of mice in different time periods by inductively coupled plasma mass spectrometry (ICP-MS), and MnCl 2 and PBS were used as analytical benchmarks. After orthotopic injection of 200 μL of FD–Mn–FD in mice, the content of Mn 2+ in the tumor site gradually decreased with time.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, oxygen-independent methods have been adopted based on anthracene derivatives which have been widely used as a 1 O 2 -storing moiety through the formation of endoperoxides (EPOs). [16][17][18][19] Notably, the stored 1 O 2 can be released thermally via cycloreversion. Therefore, EPOs were frequently coloaded with photothermal reagents, which can produce heat under photoirradiation and trigger the thermolysis of EPOs to release stored 1 O 2 .…”
Section: Doi: 101002/smll202202369mentioning
confidence: 99%
“…Therefore, EPOs were frequently coloaded with photothermal reagents, which can produce heat under photoirradiation and trigger the thermolysis of EPOs to release stored 1 O 2 . [18][19][20][21][22][23][24][25] Nevertheless, more efficient 1 O 2 storage and release systems are highly desirable for oxygen-independent ablation of hypoxic tumors.…”
Section: Doi: 101002/smll202202369mentioning
confidence: 99%
“…8,12,13 Recently, a series of organic functional systems with diphenylanthracene backbones have been constructed to implement the storage and controlled release of 1 O 2 . [14][15][16][17][18][19][20] Xiao's group used diphenylanthracene and porphyrin derivatives to prepare a covalent organic polymer which can capture the 1 O 2 produced by the photodynamic process of porphyrins and which can release 1 O 2 after heating to 110 °C. 19 Other polymer materials with diphenylanthracene units connected directly on their side chains through covalent bonds have also been synthesized for self-carrying 1 O 2 by Ling et al 18 However, being based on covalent bonds, the construction of these materials is time-consuming and cost-intensive, which will also limit the selection of diverse functional units that have better capability for 1 O 2 storage and release.…”
Section: Introductionmentioning
confidence: 99%